Central Systolic Blood Pressure Is Associated With Early Vascular Damage in Children and Adolescents With Type 1 Diabetes - Tagetti, Angela; Piona, Claudia A.; Marcon, Denise; Giontella, Alice; Branz, Lorella; Bortolotti, Stefano; Morandi, Anita; Maffeis, Claudio; Fava, Cristiano (Frontiers in Cardiovascular Medicine, 2021)
Objective of the study: This study aimed to test the effect of multiple cardiovascular risk factors on subclinical indices of atherosclerosis in children and adolescents with type 1 diabetes (T1D). Methods: Carotid intima-media thickness (cIMT), carotid distensibility coefficient (cDC), and carotid–femoral pulse wave velocity (PWV) were measured in children and adolescents with T1D, in a follow-up at the outpatient clinics of Verona. Blood pressure (BP; both central and peripheral), metabolic and other cardiovascular risk factors were evaluated in multivariate linear regressions to assess the association with the measured indices of subclinical vascular damage. Results: One hundred and twenty-six children and adolescents were included. cIMT was above the 95th percentile for age and height in 60.8% of the population, whereas 26% of the sample had cDC impairment (less than the 5th percentile) and 4.8% had an elevated PWV. Independent determinants of cIMT according to the regression models were only gender type of glucose monitoring and central systolic BP (cSBP). PWV was associated with age, sex, heart rate, and cSBP; cDC with age and both cSBP and, alternatively, peripheral BP (pBP). Neither pBP nor any of the tested metabolic parameters, including glycated hemoglobin, was associated with PWV and cIMT. Conclusions: A high proportion of early vascular damage, especially an increased cIMT, is present in children and adolescents with T1D in whom cSBP seems to be a common determinant. In children and adolescents with T1DM, a special focus should be on hemodynamic risk factors beyond metabolic ones.